Preparation and characterization of grafted imprinted monolith for capillary electrochromatography - Wei, Ze-Hui; Mu, Li-Na; Pang, Qian-Qian; Huang, Yan-Ping; Liu, Zhao-Sheng (Electrophoresis, 2012)
In this paper, a molecularly imprinted polymer (MIP) coating grafted to a trimethylolpropane trimethacrylate (TRIM) core material for CEC was reported. The core monolith was prepared with a solution of 20% (w/w) TRIM in a mixture of porogen and a polymerization precursor, which can generate a stable electroosmotic flow due to the formation of ionizable groups after postpolymerization hydrolization. Graft polymerization took place on the resultant TRIM monolith with a mixture of template, methacrylic acid, and ethylene glycol dimethacrylate. Strong recognition ability (selectivity factor was 5.83) for S‐amlodipine and resolution of enatiomers separation (up to 7.99) were obtained on the resulting grafted imprinted monolith in CEC mode. The influence of CEC conditions on chiral separation, including the composition of mobile phase, pH value, and the operating voltages was studied. These results suggest that the method of grafted polymerization reported here allows a rapid development of MIP monolith once core materials with desired properties are available, and is a good alternative to prepare CEC‐based monolithic MIPs.